Supervisory control of networked discrete event systems with timing structure - Alves, Marcos Vinícius Silva (2017)
In this work, we study the supervisory control problem of Networked Discrete Event Systems with Timing Structure (NDESWTS), that is subject to bounded communication delays and intermittent loss of observations. We assume that the communication between the plant and the supervisor is carried out through a network that can have several channels, so that, communication delays may change the order of the observations. We will propose an untimed equivalent model for NDESWTS that represents all possible implications of delays and loss of observations. For this matter, we assume a priori knowledge of the minimal transition activation time and the maximal communication delays, and also take into account possible packet losses. Based on this model, we formulate a networked supervisory control problem and present a necessary and sufficient condition for the existence of a networked supervisor. We also present a systematic way to design networked supervisors, where we use the property of relative observability in order to increase the achieved language permissiveness. In addition, another research topic addressed in this work is the concept of relative observability. In this concern, we propose new algorithms for the verification of relative observability and computation of relatively observable sublanguages, shown to be more efficient than the previous ones proposed in the literature.